Trends in Hospital Admissions for Intimate Partner Violence in Australian Mothers With Children Born From 1990 to 2009. Issue 15 (August 2021) - Orr, Carol; Preen, David; Fisher, Colleen; Sims, Scott; O'Donnell, Melissa
This study aims to determine the prevalence, and trends over time, of Western Australian (WA) mothers who were victims of intimate partner violence (IPV) requiring hospital admission. The study investigated the prevalence of all mothers and the specific prevalence of Aboriginal and non-Aboriginal mothers. A population-based cohort study using de-identified linked health data of mothers of children born from 1990 to 2009 in WA was carried out. The prevalence of hospitalizations for IPV in mothers of children born in the period 1990-2009 (per 1, 000 births) was calculated. Results indicate that the overall prevalence of hospital admissions for mothers assaulted 12 months prior to their child's birth month increased in the period 1990-2009, from 2.7 to 7.7 per 1, 000 births. There was also an increase in the overall prevalence of hospital admissions of mothers who were assaulted 12 months prior to the birth month and 36 months after the birth month, from 8.9 per 1, 000 births in 1990 to 19.4 per 1, 000 births in 2009. In addition, being Aboriginal, having a mother <30 years of age, and being of low SES significantly increased the odds of having a mother with an IPV admission. This study highlights that while there has been an increase in the prevalence of IPV admissions for mothers of children born from 1990 to 2009 in WA, the level of prevalence has remained persistent for the last decade for the whole population. However, non-Aboriginal mothers have seen an increase in prevalence in the last decade. This increase is associated with the introduction of the Z63.0 code in International Statistical Classification of Diseases and Related Health Problems, Tenth Revision, Australian Modification (ICD-10-AM). This study highlights the importance of prioritizing groups for targeted early intervention and prevention as well as the need for culturally appropriate strategies to reduce the burden of interpersonal violence.